Investigating the Influence of Penetration Length of Cut-off Wall on its Dynamic Interaction with Core and Foundation of Earth Dam - Javanmard, Mehran; Mottaghi, Reza; Hosseini, S. M. Mir Mohammad (Salehan Institute of Higher Education, 2018)
Seepage and flow of water in the soil is one of the most important issue and effective elements in designing embankment dams. One of the methods to control seepage in alluvial foundation of earth dams is to use a plastic concrete cutoff-wall. For better seepage control, the cutoff-wall extends inside the clayey core as the one of common method of connection of cut-off wall and the core. Due to the stiffness difference of the core material and cutoff-wall, and also due to geological situation, physical and mechanical properties of rock and foundation, interaction of core and foundation with cut-off wall in different static and dynamic load cases is very considerable. Failure of cut-off wall occurs in cut-off wall and core joint.Â So the study of their interaction, especially during an earthquake is very important. Karkheh dam cut-off wall with an area of about 150000 m2 is chosen for this study. FLAC software has been used to study the effect of cutoff-wall penetration length variation, inside the clay core of Karkheh earth dam under dynamic loading.Â In numerical analysis of Karkheh earth dam model, all construction stages and seepage through dam are modelled. The model is first calibrated according to the results obtained from the dam instrumentations. After calibrating, according to available seismic studies of region, a suitable acceleration was selected and applied to the model. In this research, in order to find the optimum length, the effect of 0, 5, 10, 15 and 20 meters penetration length of cut-off wall in aforementioned conditions has been investigated. The results of the numerical study showed that the horizontal displacement and the maximum shear strain in the cutoff-wall is occurred adjacent to the clay core and the interface of core and foundation is a critical point for the cut-off wall, and also the stress in cut off wall joint increases with the elongation of penetration depth of the wall.